New Insights into the Correlation between Secondary Traumatic Stress and Cognitive Flexibility in Mental Health Therapists and Counselors - Durak, Hilal; Çelik, Emel Gökçen; Çelik, Bilge (Journal of Ethnic and Cultural Studies, 2025)
Mental health professionals regularly witness their clients' challenging life events, which they must cope with throughout their careers. This study examines the association between secondary traumatic stress (STS) and cognitive flexibility among counselors and therapists and explores their variations by demographic and professional factors. The participants included 536 professionals (psychiatrists, psychologists, social workers, and child development specialists). Secondary traumatic stress and cognitive flexibility were assessed using the Secondary Traumatic Stress Scale and the Cognitive Control and Flexibility Scale, respectively. Demographic data were collected using the Personal Data Form. SPSS 21.0 software was used for data analysis. Pearson correlation analysis revealed a moderate negative association between the participants' STS and cognitive flexibility levels. The findings indicated a higher STS risk among child development specialists, younger professionals, those who are single or do not have children, those who have lower income or fewer years of experience, and those without trauma-related training or supervision. Conversely, older age, marriage, children, higher income, higher level of education, longer experience, and trauma-related training were identified as protective factors for cognitive flexibility. Several recommendations were provided to strengthen mental health professionals’ flexibility and reduce the impact of STS on them. First, supportive measures in protection, prevention, and treatment for mental health professionals who work in the field of trauma should be taken. Second, priority should be given to extending certified training programs that will improve the professional skills of mental health workers. Third, counselors should be supported by peer, individual, and group supervision. Finally, examining gender- specific risks is essential to increase women's cognitive flexibility and improve their physical and emotional well-being.